Acellular Porcine Cornea Produced by Supercritical Carbon Dioxide Extraction: A Potential Substitute for Human Corneal Regeneration. Issue 3 (23rd March 2022) - Liang, Chang-Min; Hsieh, Dar-Jen; Tseng, Fan-Wei; Srinivasan, Periasamy; Yeh, Ming-Long; Tai, Ming-Cheng
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Purpose: The aim of this study was to develop a non-cytotoxic, biocompatible innovative acellular porcine cornea (APC) for corneal wound healing and corneal blindness treatment. Methods: APC was produced by using supercritical carbon dioxide (SCCO2 ) to decellularize the porcine cornea. Decellularization of the porcine cornea was examined by hematoxylin and eosin staining and 4, 6-diamidino-2-phenylindole, dihydrochloride staining. The residual DNA content of APC was analyzed in comparison with the native porcine cornea. Virus inactivation up to at least 6 log10 was confirmed for the stepwise process of APC for 4 different model viruses. In addition, a series of in vitro and in vivo tests in accordance with ISO-10993 biocompatibility assay and animal performance tests were performed. Results: APC produced by the SCCO2 process revealed complete decellularization, without any residual non-collagenous proteins. The scanning electron microscopy structural features of the decellularized cornea were similar to those of human. APC was found to be nontoxic and exhibited excellent biocompatibility in both in vitro and in vivo studies. The animal performance test proved that APC exerted excellent adaptability on the cornea and no sign of irritation and good compatibility in lamellar corneal transplantation. Conclusions: APC manufactured by SCCO2 technology revealed complete cells and non-collagenous protein removal compared with the Triton–sodium dodecyl sulfate decellularization process. APC showed excellent biocompatibility in rabbit lamellar corneal transplantation with a follow-up to 1 year. APC can be a potential substitute for human-donated cornea for corneal transplantation in the near future.